Network pharmacology and molecular docking analyses of the Wuwei Mingmu formula indicate that IL-10 and IL-6 are critical targets against experimental autoimmune uveitis in rats - Liang, Xing; Zhang, Junkun; Yuan, Fang; Liang, Li; Li, Jie; Duan, Yajian (Frontiers in Pharmacology, 2025)
ObjectivesIn this study, we analyzed the use of the Wuwei Mingmu formula (WMF) for treating experimental autoimmune uveitis (EAU) based on a network pharmacology approach.MethodsWe obtained an integrated gene set between WMF and EAU using the TCMSP database and GeneCards database. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, and protein-protein interaction (PPI) network analyses were used to elucidate possible therapeutic mechanisms. Moreover, the relationships among the herbal composition, active ingredients, therapeutic targets, and critical cell signaling pathways used to treat EAU were analyzed. Molecular docking was performed to elucidate the patterns of interactions between the active compounds and the targeted proteins. EAU rat models were constructed to examine the therapeutic efficacy of WMF in vivo.ResultsAn integrated gene set of 30 genes was acquired. The results of the GO and KEGG analyses indicated that WMF could regulate immune responses and vascular functions during EAU treatment. The PPI network and subnetworks confirmed the presence of 15 hub genes. A network pharmacology map was drawn to understand the complex relationships among herbs, active compounds, targets, and signaling pathways. Additionally, molecular docking was performed on genes with the highest significance (IL-10 and IL-6), representing T-helper activation in immune-mediated uveitis. The active compounds of WMF rapidly docked with IL-10 and IL-6 in the grid box. The results of the in vivo assays revealed that WMF treatment significantly attenuated the pathological changes in EAU rat eyes and alleviated the inflammatory response. Moreover, the increase in the level of IL-6 in EAU rats decreased after WMT stimulation, whereas the IL-10 levels increased in EAU rats after WMF treatment.ConclusionWMF can be used to treat EAU as it can modulate immune responses and vascular functions. IL-10 and IL-6 are the main therapeutic targets of WMF, and the herbal composition of WMF can be further optimized to increase its therapeutic efficacy.